2023
DOI: 10.1186/s12960-023-00811-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of physical violence against doctors in Bangladeshi tertiary care hospitals

Abstract: Background The increasing physical violence against doctors in the health sector has become an alarming global problem and a key concern for the health system in Bangladesh. This study aimed to determine the prevalence and associated factors of physical violence against doctors in Bangladeshi tertiary care hospitals. Methods A cross-sectional survey was performed among 406 doctors working in tertiary care hospitals. Data were collected using a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Additionally, shortages of medicines and supplies, dissatisfaction with treatment, care delays, inadequate security and unrealistic patient expectations contribute to this situation 25 26. Previous studies have revealed profound impacts of WPV on healthcare professionals, including a strong desire to leave the profession, job dissatisfaction, decreased work performance, work–life imbalance, feelings of anger, depression, fear, stress, loss of self-confidence, suicidal tendencies and a diminished quality of life 12 13 21. These findings underscore the complex and severe repercussions of WPV, affecting both the professional and personal spheres of individuals in the healthcare sector.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, shortages of medicines and supplies, dissatisfaction with treatment, care delays, inadequate security and unrealistic patient expectations contribute to this situation 25 26. Previous studies have revealed profound impacts of WPV on healthcare professionals, including a strong desire to leave the profession, job dissatisfaction, decreased work performance, work–life imbalance, feelings of anger, depression, fear, stress, loss of self-confidence, suicidal tendencies and a diminished quality of life 12 13 21. These findings underscore the complex and severe repercussions of WPV, affecting both the professional and personal spheres of individuals in the healthcare sector.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, being a male doctor, serving in entry-level positions such as intern doctors and emergency duty doctors, and working in public hospitals were found to have higher associations with exposure to WPV 11. Another nationwide study in Bangladesh revealed that 12.3% of physicians employed in tertiary hospitals encountered physical violence and over 70% of victims identified patient’s relatives as the primary instigators 13. While previous studies have addressed the prevalence, associated factors, consequences and instigators of WPV among healthcare professionals, our study focused specifically on a vulnerable subgroup: physicians in training or in the early to mid-level stages of their careers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health sector encompasses various jobs, ranging from home care aid to hospital services; therefore, it poses risks of violence due to interaction between HWs and patients [ 2 , 3 ]. A shocking finding revealed by international studies is that the health system has the highest risk of WPV [ 1 4 ] and in some cases, causes physical injuries and even death among HWs [ 4 7 ]. Even more concerning is that the severity of these injuries and fatalities is prevalent in both developed and developing countries [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A shocking finding revealed by international studies is that the health system has the highest risk of WPV [ 1 4 ] and in some cases, causes physical injuries and even death among HWs [ 4 7 ]. Even more concerning is that the severity of these injuries and fatalities is prevalent in both developed and developing countries [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%